Assessment of the efficacy of biodegradable sanitary pads: a cross-sectional survey study among college students and staff at South Goa - Bale, Anura; Patki, Geeta; Lotliker, Madhuri; Upadhye, Gandhali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Menstruation is an absolute physiological event. Menstrual management program is a wide concept worldwide. Many aids are presently available in the market too. Each one has its own positive and negative impacts. Biodegradable sanitary napkins have sparked interest in theo- thinkers as well as users. However, limited research exists on the effectiveness of biodegradable sanitary napkins. Understanding this purview, a study was conducted with the aim to evaluate the effectiveness of biodegradable sanitary napkins among the youngsters. Methods: A cross-sectional survey was conducted among 150 female college students, along with staff from the reproductive phase, who were willing to participate. Participants provided feedback on their experiences with biodegradable sanitary napkins. Females who were known cases of genital infections were excluded from the study. After verbal consent subjects were enrolled in the study. Collection of data was done through Google forms with consent. Results: The study concluded that 68.7% females managed their menstrual flow with these sanitary pads and also indicated that the use of sanitary pads 94.7% subjects did not experience any allergy. Conclusions: The findings of this survey of biodegradable sanitary pads revealed overall satisfaction and minimal side effects. The study also indicated a need for product innovation in comfort, skin safety, and flow management.